Kepastian Hukum Terkait Kewajiban Pengurusan Izin Menggunakan Tenaga Kerja Asing Dan Penerapannya - Syafita Shafira (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2021)
This research discusses legal certainty regarding the obligation to obtain permits to use foreign workers (IMTA) as regulated in Law Number 13 of 2003 concerning manpower, and knows the judges' considerations in the decision Number 51 / Pdt.G / 2015 / PN.bil between the plaintiff named G Raymond Pical and the defendant, namely PT. A. Schulman International. In addition, to find out how to solve the problems of foreign workers who work in Indonesia without a permit to employ foreign workers (IMTA). The results of this thesis research show that the consideration of the District Court judges in the case of using foreign workers based on the judex facti examination at the Bangil District Court is correct but not sufficient because in this consideration the judge did not sanction the defendant because the defendant employed foreign workers without an IMTA permit as already written in Law Number 13 of 2003.Keywords: Legal Certainty; Foreign workers; Law Number 13tahun 2003